Interpretation of crank torque during an all-out cycling exercise at high pedal rate - Capmal, S.; Vandewalle, H. (Sports Engineering, 2010)
The use of cycle ergometers with strain gauges bonded on to the cranks enables the evaluation of strength, velocity and power. However, the torque measured at the end of downstroke is higher at high velocity than at medium velocity in contradiction with the force-velocity relationship. Kinematic data were collected with a camera during sprints on a Lode ergometer with strain gauges. Leg mechanical energy (E Leg) and its derivative (dE Leg/dt) were calculated from the sum of the kinetic and potential energies. The opposition of P ext (output at crank level) and dE Leg/dt before bottom dead centre suggested a transformation of E Leg into external work, explaining the higher torque at the end of downstroke at peak velocity. Another explanation is that the leg muscles worked on different parts of their torque-angle relationships as the phase between knee and ankle angles was different at low and high cycling frequencies. Musculo-skeletal net power output (algebraic sum of P ext and dE Leg/dt) indicated that musculo-skeletal structures participated in the upward movement, whereas P ext was negative.